Protective effect of melatonin on antioxidative system in experimental ischemia-reperfusion of rat small intestine - Ustundag, B; Kazez, A; Demirbag, M; Canatan, H; Halifeoglu, I; Ozercan, IH (Cell Physiol Biochem Press Gmbh & Co, 2000)
Aims: Effect of exogenously administered melatonin (N-acetyl 5-methoxytryptamine) on antioxidant systems in experimental Ischemia-Reperfusion (I-R) of rat gastrointestinal system (GIS) was examined. Methods: A total of 40 rats were divided into 4 groups: Group 1 (Sham), Group 2 (I-R), Group 3 (I-R +10 mg/ kg melatonin) and Group 4 (I-R + 20 mg/kg melatonin). Activity levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were determined in small intestines. Results, There was a significant (p<0.05) reduction in GSH-Px levels in Group 2 (64.16+/-7.02 U/mg protein) compared to Group 1 (80.15+/-9.32 U/mg protein). We observed a meaningful increase in GSH-Px levels in melatonin applied groups (Group 3. 75.94+/-9.83 U/mg protein, Group 4, 78.55+/-9.11 U/mg protein) compared to Group 2, Correspondingly, SOD activity levels were significantly reduced (p<0.001) in Group 2 (24.14+/-4.35 U/mg protein) compared to controls (52.91+/-6.13 U/mg protein). A stronger effect (p<0.001) of melatonin was observed on SOD levels compared to GSH-Px levels in both doses (Group 3. 38.96+/-6.39 U/mg protein, Group 4. 43.07+/-7.76 U/mg protein). Levels of selenium were reduced significantly in Group 2 (1.11+/-0.31 g/g tissue) compared to Group 1 (2.01+/-0.19 mug/g tissue). Melatonin application in Group 3 (1.13+/-0.28 mug/g tissue) and Group 4 (1.89+/-0.48 mug/g tissue) caused an increase in selenium levels. There was a strong correlation between increases in selenium and GSH-Px levels in Group 4 (0,0.651 p<0.01). Conclusions: Melatonin seems to exert its antioxidant effect in GIS tract by stimulating SOD and GSH-Px. Selenium also seems to have an antioxidant contribution on protecting rat gastrointestinal tract I-R injury. Copyright (C) 2000 S. Karger AG, Basel.
Keywords: ischemia-reperfusion; SOD; GSH-Px; selenium; antioxidants